The Cambridge introduction to Samuel Beckett - McDonald, Ronan (Cambridge University, 2013)
This book is an accessible introduction to one of the most important writers of the twentieth century. It provides biographical and contextual information, but more fundamentally, it considers how we might think about an enduringly difficult and experimental novelist and playwright who often challenges the very concepts of meaning and interpretation. It deals with Beckett's life, intellectual and cultural background, plays, prose, and critical response and relates his work and vision to the culture and context in which he wrote.